ANALYSIS OF THE INFLUENCE OF LIQUIDITY LEVEL AND PROFITABILITY ON STOCK PRICES OF SHARIA COMPANIES LISTED IN JAKARTA ISLAMIC INDEX (JII) 2017-2019 - azma, Yuhani; Novi Mubyarto (Lembaga Pengembangan Kinerja Dosen, 2022)
This research aims to determine the effect of liquidity and profitability on stock prices in Islamic companies listed in the JII in 2017-2019. This study uses independent variables of liquidity and profitability, variables depending on stock prices, secondary data in financial statements in Islamic companies listed in the JII in 2017-2019, and research in descriptive quantitative approaches. The analytical tool used is multiple linear analysis. The result of this study is that the ratio of liquidity and profitability affects the stock price; using the F test of independent variables influence simultaneously against dependent variables, the overall calculation shows that the independent variable explained against the dependent variable by the remaining 65.5% influenced by other variables that were not examined in this study.